Crime and terrorism - Grabosky, Peter N. (Compact criminology, 2010)
Terrorism and crime are two areas of knowledge that have traditionally been looked at independently. In this timely and original text, two of the leading authors in the field provide a clear and thorough look at terrorism from a criminological perspective. Integrating the latest research, the book explores the motives of criminals and terrorists, the causes of crime and terrorism and the impact of the law and the legal system. Central to this exploration, the authors examine the nexus between criminal and terrorist organizations, and the commonalities and differences between them and what this means for public policy and safety and security within states. Cross-cultural and international in perspective, this is a fresh and original text that will appeal to undergraduates, academics, and researchers in criminology, politics, international relations, sociology, communication and cultural studies--Product description.